Vascular smooth muscle cell hypertrophy vs. hyperplasia. Autocrine transforming growth factor-beta 1 expression determines growth response to angiotensin II. - Gibbons, G H (1992)
Recent observations in our laboratory suggest that angiotensin II (Ang II) is a bifunctional vascular smooth muscle cell (VSMC) growth modulator capable of inducing hypertrophy or inhibiting mitogen-stimulated DNA synthesis. Because transforming growth factor-beta 1 (TGF beta 1) has similar bifunctional effects on VSMC growth, we hypothesized that autocrine production of TGF beta 1 may mediate the growth modulatory effects of Ang II. Indeed, this study demonstrates that Ang II induces a severalfold increase in TGF beta 1 mRNA levels within 4 h that is dependent on de novo protein synthesis and appears to be mediated by activation of protein kinase C (PKC). Ang II not only stimulates the synthesis of latent TGF beta 1, but also promotes its conversion to the biologically active form as measured by bioassay. The coincubation of VSMCs with Ang II and control IgG has no significant mitogenic effect. However, the co-administration of Ang II and the anti-TGF beta 1 antibody stimulates significantly DNA synthesis and cell proliferation. We conclude that: (a) Ang II induces increased TGF beta 1 gene expression via a PKC dependent pathway involving de novo protein synthesis; (b) Ang II promotes the conversion of latent TGF beta 1 to its biologically active form; (c) Ang II modulates VSMC growth by activating both proliferative and antiproliferative pathways; and (d) Autocrine active TGF beta 1 appears to be an important determinant of VSMC growth by hypertrophy or hyperplasia.